A frost-resistant concrete and a method for producing the same

CN118619625BActive Publication Date: 2026-10-30CHINA ENERGY CONSTR GRP NORTHWEST ELECTRIC POWER CONST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410735079.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2026-10-30
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

[0003]我国地域辽阔,大部分地区的年平均气温变化极大,尤其是在季节交替的时候,昼夜温差变化更加明显,尤其是当气温不断在冰点上下变化时,气温变化会导致混凝土毛细孔中含有的水分不断冻结融化,当混凝土处于饱水状态时,混凝土毛细孔中的水在结晶时会产生膨胀压力,从而破坏、挤压混凝土的内部结构导致混凝土出现微裂缝,而在反复冻融过程中,混凝土的微裂缝会逐渐增长、扩大,进一步破坏混凝土结构,严重影响混凝土的耐久性,从而严重影响混凝土建筑的工程质量

Benefits of technology

1、本申请中聚丙烯腈纤维的弹性模量随温度的降低而提高,对于混凝土在低温环境下抵抗冻胀破坏具有正面增强效应,而且其具有阻裂作用,可以抵挡混凝土内部因受到冻融破坏所产生的微裂纹的扩展,从而可以提高混凝土的抗冻融性能,引气剂的添加使得混凝土内部均匀分布微小气泡,能够缓解混凝土的冻胀压力,提高混凝土抗冻性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004881479380000091
    Figure BDA0004881479380000091
Patent Text Reader

Abstract

The application relates to the field of concrete, and particularly discloses an anti-freezing concrete and a preparation method thereof. The concrete comprises the following raw materials: cement, coarse aggregate, fine aggregate, water, mineral powder, fly ash, an additive, an anti-freezing agent, an air entraining agent, waste aluminum particles, a silane coupling agent, polyacrylonitrile fiber and thermal expansion microspheres; the core material of the thermal expansion microspheres is polyacrylonitrile fiber powder and liquid alkane, and the wall material is a mixture of polyurea and polyvinyl chloride; the preparation method comprises the following steps: mixing the cement, the coarse aggregate, the fine aggregate, the mineral powder, the fly ash, the air entraining agent, the waste aluminum particles and the polyacrylonitrile fiber to prepare an initial mixture; mixing the additive and the anti-freezing agent, then adding the additive and the anti-freezing agent into water, then adding the silane coupling agent, then adding the initial mixture after mixing, and finally adding the thermal expansion microspheres to prepare the anti-freezing concrete after stirring. The application has the characteristics of improving the anti-freezing and thawing performance of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of concrete, and more specifically, to a freeze-resistant concrete and a method for preparing the same. Background Technology

[0002] Concrete is a porous composite material composed of cement, sand, and stone. To ensure good workability during concrete construction, more mixing water is always added to the concrete than the hydration water required for the cement. This excess water remains in the concrete as free water, forming interconnected capillaries that occupy a certain volume. These interconnected capillaries are the main cause of frost damage to concrete.

[0003] my country has a vast territory, and the average annual temperature varies greatly in most areas, especially during seasonal transitions when the temperature difference between day and night is even more pronounced. In particular, when the temperature fluctuates around the freezing point, the water contained in the capillaries of concrete will continuously freeze and thaw. When the concrete is saturated, the water in the capillaries will generate expansion pressure when it crystallizes, which will damage and compress the internal structure of the concrete, causing micro-cracks to appear. In the process of repeated freeze-thaw cycles, the micro-cracks in the concrete will gradually grow and expand, further damaging the concrete structure and seriously affecting the durability of the concrete, thus seriously affecting the engineering quality of concrete buildings.

[0004] Therefore, improving the freeze-thaw resistance of concrete is of great significance for concrete applications. Summary of the Invention

[0005] To improve the freeze-thaw resistance of concrete, this application provides a freeze-resistant concrete and a method for preparing the same.

[0006] In a first aspect, this application provides a frost-resistant concrete, which adopts the following technical solution: A type of frost-resistant concrete comprises the following raw materials in parts by weight: 200-300 parts cement, 800-950 parts coarse aggregate, 700-850 parts fine aggregate, 100-120 parts water, 60-80 parts mineral powder, 40-60 parts fly ash, 1-3 parts admixture, 1-3 parts antifreeze agent, 0.5-3.5 parts air-entraining agent, 0-10 parts waste aluminum particles, 3-8 parts silane coupling agent, 30-50 parts polyacrylonitrile fiber, and 20-40 parts thermally expandable microspheres; The core material of the thermally expanded microspheres is polyacrylonitrile fiber powder, lignocellulose powder and liquid alkanes, and the wall material is a mixture of polyurea and polyvinyl chloride.

[0007] By adopting the above technical solutions, the elastic modulus of polyacrylonitrile fiber in this application increases with decreasing temperature, which has a positive enhancing effect on the resistance of concrete to frost heave damage in low-temperature environments. Moreover, it has a crack-inhibiting effect, which can resist the propagation of microcracks caused by freeze-thaw damage inside the concrete, thereby improving the freeze-thaw resistance of the concrete. The addition of air-entraining agent makes the micro-bubbles evenly distributed inside the concrete, which can alleviate the freeze-thaw pressure of the concrete and improve the freeze-thaw resistance of the concrete. The addition of waste aluminum particles in this application helps to improve the compressive strength and flexural strength of the concrete, thereby helping the concrete resist the expansion stress caused by water freezing in freeze-thaw cycles. Moreover, it has good thermal conductivity and high heat capacity, which to a certain extent affects the heat transfer and distribution of the concrete during the freeze-thaw process. Finally, it was found that the addition of waste aluminum concrete also has a certain positive effect on the freeze-thaw resistance of concrete.

[0008] In addition, this application also incorporates thermally expandable microspheres. The core material of these microspheres contains liquid alkanes with low boiling points. These alkanes vaporize at temperatures above room temperature, generating internal pressure that drives the microspheres to expand. At low temperatures, they remain liquid, giving the microspheres certain low-temperature shrinkage and high-temperature expansion properties. When water in concrete freezes during low-temperature cooling, the expansion of the water exerts pressure on the concrete. The contraction of the thermally expandable microspheres at this time buffers the water expansion, reducing the pressure on the concrete. When the ice crystals melt, the concrete shrinks again. At this point, the vaporization of the liquid alkanes in the microspheres drives the microspheres to expand, compensating for the shrinkage caused by the melting of water. This reduces cracking caused by expansion and contraction during freeze-thaw cycles, improving the freeze-thaw resistance of the concrete and reducing cracking after freeze-thaw cycles.

[0009] Furthermore, polyacrylonitrile fibers are prone to agglomeration under high-temperature conditions. The exothermic reaction of cement hydration affects the distribution of polyacrylonitrile fibers in concrete and can also cause deformation of the fibers, reducing their crack-resistant effect and limiting their freeze-thaw resistance. In this application, the addition of thermally expanding microspheres can improve the high-temperature resistance of the concrete by enhancing the high-temperature resistance of the wall material. In addition, the thermally expanding microspheres have a certain compression and restraining effect on the polyacrylonitrile fibers during high-temperature expansion, thereby reducing their deformation during hydration and improving the freeze-thaw resistance of the final concrete. The addition of silane coupling agent improves the compatibility of the fibers and thermally expanding microspheres with the concrete system, which helps to improve their uniform dispersion and thus improve the freeze-thaw resistance.

[0010] Optionally, the liquid alkane may be n-pentane or a mixture of n-pentane and n-hexane.

[0011] By adopting the above technical solution, n-pentane has a boiling point of 36℃. When liquid alkanes containing n-pentane are selected, the resulting thermally expanding microspheres can achieve low-temperature shrinkage and high-temperature expansion to compensate for the cracking problem caused by water freeze-thaw expansion in concrete. Moreover, its low boiling point allows the microspheres in the concrete to expand to a certain extent during cement hydration. After hydration and solidification, the temperature drops slightly. Combined with the action of air-entraining agents, a certain closed-cell structure is formed in the concrete, which can buffer the volume changes and internal stress changes caused by the freeze-thaw cycle of concrete, thereby helping to improve the freeze-thaw resistance of concrete.

[0012] Optionally, the thermally expanded microspheres are prepared by the following method: Polyacrylonitrile fiber was crushed and ground to obtain polyacrylonitrile fiber powder. Then, liquid alkane was added at low temperature, and the mixture was impregnated for 2-4 hours under vacuum ultrasonic assistance and then filtered to obtain a core material mixture. Polyurea and polyvinyl chloride were dissolved in tetrahydrofuran to prepare a wall material solution. The wall material solution was then spray-dried onto a core material mixture to obtain thermally expanded microspheres.

[0013] By adopting the above technical solution, polyurea and polyvinyl chloride (PVC) are selected as wall materials, with PVC as a thermoplastic polymer. This adapts to the volume distribution changes of the core material, polyacrylonitrile fiber powder, and liquid alkanes due to temperature variations. Polyurea exhibits higher thermal stability and mechanical strength, resulting in thermally expandable capsules with better mechanical strength and thermal stability. After impregnation of the polyacrylonitrile fiber powder in liquid alkanes, the liquid alkanes are wetted into the pores of the fiber powder. Following spray drying, microspheres with polyacrylonitrile fiber and liquid alkanes as the core material are obtained.

[0014] Optionally, the mass ratio of the core material mixture to the wall material solution is 1:(0.6-0.8); the polyacrylonitrile fiber powder is completely immersed in liquid alkane, the mass ratio of polyurea to polyvinyl chloride is 1:(0.6-0.8), and the amount of tetrahydrofuran added is 4-5 times the mass of polyurea.

[0015] Optionally, when impregnating the polyacrylonitrile fiber powder in liquid alkane, the liquid alkane is added and the process is carried out at an ambient temperature of 5-15℃, with the following vacuum ultrasonic conditions: vacuum degree of 2-5 Pa and ultrasonic frequency of 20-30 kHz.

[0016] By adopting the above technical solution, when polyacrylonitrile fiber powder is impregnated in liquid alkanes, the impregnation effect of liquid alkanes on polyacrylonitrile fiber powder is promoted under ultrasonic vacuum conditions.

[0017] Optionally, when preparing thermally expandable microspheres, when impregnating polyacrylonitrile fiber powder in liquid alkane, a mixed solvent of hydroxyl silicone oil and fluorocarbon surfactant and polysorbate is added, and the mass ratio of hydroxyl silicone oil, fluorocarbon surfactant and polysorbate is 1:(2-3):(1-2), and the mixed solvent is 3-5 wt% of the amount of polyacrylonitrile fiber powder added.

[0018] By adopting the above technical solution, the addition of hydroxyl silicone oil forms a lubricating film between polyacrylonitrile fiber powder and liquid alkanes such as n-pentane, reducing the surface tension of both and promoting the wetting effect of liquid alkanes on polyacrylonitrile fiber powder. Fluorocarbon surfactants and polysorbates further reduce the interfacial tension between the two and promote the wetting effect of liquid alkanes on polyacrylonitrile fiber powder.

[0019] Optionally, a primary thermal expansion microsphere is prepared by spray drying the wall material solution onto the core material mixture, and then sodium alginate is dissolved in water and spray dried onto the surface of the primary thermal expansion microsphere to form thermal expansion microspheres.

[0020] By adopting the above technical solution, after the primary thermal expansion microspheres are prepared, they are further coated with sodium alginate wall material, which improves the dispersion uniformity of the thermal expansion microspheres in concrete and further improves the freeze-thaw resistance of concrete. Moreover, when added to concrete, the sodium alginate wall material dissolves under stirring conditions, reducing mechanical damage to polyurea and polyvinyl chloride wall materials and reducing mechanical damage to the thermal expansion microspheres, thereby playing a role in compensating for expansion and contraction.

[0021] Optionally, the mass ratio of sodium alginate to water is 1:(8-10), and the mass ratio of the mixture of sodium alginate and water to the wall material solution formed by polyurea, polyvinyl chloride and tetrahydrofuran is 1:(0.8-1.2).

[0022] Optionally, the coarse aggregate is selected as crushed stone with a continuous particle size of 5-30mm, the fine aggregate is selected as sand with a coefficient modulus of 2.6-3.2, the fly ash is selected as Class I fly ash of type F, and the mineral powder is selected as S95 grade mineral powder.

[0023] Optionally, the admixture is a polycarboxylate superplasticizer, and the air-entraining agent is a rosin-based air-entraining agent.

[0024] By adopting the above technical solution, polycarboxylate superplasticizers can significantly reduce the water-cement ratio of concrete, meaning that with the same amount of cement, the amount of water used in concrete is reduced. The lower water-cement ratio helps reduce the content of freezeable water in concrete, thereby reducing the expansion stress caused by water freezing during freeze-thaw cycles and improving the frost resistance of concrete.

[0025] Secondly, this application provides a method for preparing frost-resistant concrete, which adopts the following technical solution: A method for preparing frost-resistant concrete includes the following steps: A preliminary mixture is prepared by mixing cement, coarse aggregate, fine aggregate, mineral powder, fly ash, air-entraining agent, waste aluminum particles, and polyacrylonitrile fiber. After mixing the admixture and antifreeze agent, add them to water, then add the silane coupling agent, mix again, add the initial mixture, and finally add the thermal expansion microspheres. After stirring, antifreeze concrete is obtained.

[0026] By adopting the above technical solution, the preparation method of this application is simple and convenient, and easy to industrialize. Moreover, the final heating and expansion of the microspheres reduces the damage to the thermally expanded microspheres during the stirring process, ensuring their integrity and workability.

[0027] In summary, this application has the following beneficial effects: 1. The elastic modulus of the polyacrylonitrile fiber in this application increases as the temperature decreases, which has a positive enhancing effect on the concrete's resistance to frost heave damage in low-temperature environments. Moreover, it has a crack-resistant effect, which can resist the expansion of microcracks caused by freeze-thaw damage inside the concrete, thereby improving the concrete's freeze-thaw resistance. The addition of the air-entraining agent makes the micro air bubbles evenly distributed inside the concrete, which can alleviate the frost heave pressure of the concrete and improve the concrete's freeze-thaw resistance. 2. The addition of waste aluminum particles in this application helps to improve the compressive strength and flexural strength of concrete, thereby helping the concrete resist the expansion stress caused by water freezing during freeze-thaw cycles. Moreover, it has good thermal conductivity and high heat capacity, which to some extent affects the heat transfer and distribution of concrete during freeze-thaw processes. Finally, it was found that the addition of waste aluminum concrete also has a certain positive effect on the freeze-thaw resistance of concrete. 3. This application also includes thermally expandable microspheres. The core material of the thermally expandable microspheres contains liquid alkanes with low boiling points. These alkanes vaporize at temperatures above room temperature, generating internal pressure that drives the microspheres to expand. At low temperatures, they remain liquid, giving the thermally expandable microspheres certain low-temperature shrinkage and high-temperature expansion properties. When water in concrete freezes during the low-temperature cooling process, the water expansion exerts pressure on the concrete. At this time, the contraction of the thermally expandable microspheres has a certain buffering effect on the water expansion, thereby reducing the pressure of water expansion on the concrete. When the ice crystals in the concrete melt, they shrink again. At this time, the vaporization of the liquid alkanes in the thermally expandable microspheres drives the microspheres to expand, compensating for the shrinkage caused by the melting of water. This reduces the cracking phenomenon caused by the expansion and contraction of water during the freeze-thaw process, improves the freeze-thaw resistance of concrete, and reduces cracking after freeze-thaw. 4. The addition of thermally expandable microspheres in this application can improve the high-temperature resistance of the wall material and enhance the high-temperature resistance of concrete. In addition, the thermally expandable microspheres have a certain compression and restraining effect on the polyacrylonitrile fibers during high-temperature expansion, thereby reducing their deformation during hydration and improving the freeze-thaw resistance of the final concrete. The addition of silane coupling agent improves the compatibility of the fibers and thermally expandable microspheres with the concrete system, which helps to improve their uniform dispersion and thus improve the freeze-thaw resistance. Detailed Implementation

[0028] The following detailed description of this application is provided in conjunction with the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments are all from commercially available sources.

[0029] The waste aluminum particles in the following examples and preparation examples are raw aluminum waste generated during the casting of aluminum alloys, with an aluminum content of 98.5%; the polyurea used is polyurea resin from Shandong Lingchuang Biotechnology Co., Ltd. The polyvinyl chloride (PVC) used is SG-5 type PVC resin from Zibo Anhao Chemical Co., Ltd. The polyacrylonitrile fibers used are short-cut polyacrylonitrile fibers with a length of 6-12mm and a diameter of 15±2μm, sourced from Taian Songze Composite Materials Co., Ltd.

[0030] The fluorocarbon surfactant selected was TF281 from Shanghai Futian Chemical Technology Co., Ltd.; the hydroxyl silicone oil selected was MSD-6011 cationic hydroxyl silicone oil emulsion from Qingdao Meiside Organosilicon Co., Ltd.

[0031] Ordinary Portland P.O42.5 cement is used; fly ash is Class F, Grade I fly ash; mineral powder is Grade S95 mineral powder; coarse aggregate is crushed stone with a continuous particle size of 5-30mm; fine aggregate is sand with a modulus of 2.6-3.2; sodium rosinate air-entraining agent is used; high-performance polycarboxylate water-reducing agent, model D0001, purchased from Langfang Shenqi Energy Saving Technology Co., Ltd., is used; and early-strength antifreeze agent, model TW-FD1, purchased from Shijiazhuang Yingshan Chemical Technology Co., Ltd., is used.

[0032] The following preparation examples are examples of the preparation of thermally expandable microspheres. Preparation Example 1 A method for preparing thermally expandable microspheres includes the following steps: S1. Using 1 kg of polyacrylonitrile fiber as the processing standard, the polyacrylonitrile fiber is crushed and ground to obtain polyacrylonitrile fiber powder with a particle size of 0.5-1.5 mm. S2. Then, at an ambient temperature of 10°C, liquid alkane n-pentane was added to the polyacrylonitrile fiber powder. The n-pentane completely submerged the polyacrylonitrile fiber powder. After impregnation for 3 hours under vacuum ultrasonic-assisted conditions (the ultrasonic generator was started under vacuum), the core material mixture was obtained by filtration. The vacuum ultrasonic conditions were: vacuum degree of 3 Pa and ultrasonic frequency of 25 kHz. S3. Polyurea and polyvinyl chloride are mixed in a mass ratio of 1:0.7 and dissolved in tetrahydrofuran to prepare a wall material solution. The wall material solution is then spray-dried onto the core material mixture to obtain thermally expandable microspheres.

[0033] The mass ratio of the core material mixture to the wall material solution is 1:0.7, and the amount of tetrahydrofuran added is 4 times the mass of polyurea.

[0034] Preparation Example 2 A method for preparing thermally expandable microspheres includes the following steps: S1. Using 1 kg of polyacrylonitrile fiber as the processing standard, the polyacrylonitrile fiber is crushed and ground to obtain polyacrylonitrile fiber powder with a particle size of 0.5-1.5 mm. S2. Then, at an ambient temperature of 5°C, liquid alkane n-pentane was added to the polyacrylonitrile fiber powder. The n-pentane completely submerged the polyacrylonitrile fiber powder. After impregnation for 2 hours under vacuum ultrasonic-assisted conditions (the ultrasonic generator was started under vacuum), the core material mixture was obtained by filtration. The vacuum ultrasonic conditions were: vacuum degree of 2 Pa and ultrasonic frequency of 20 kHz. S3. Polyurea and polyvinyl chloride are mixed in a mass ratio of 1:0.6 and dissolved in tetrahydrofuran to prepare a wall material solution. The wall material solution is then spray-dried onto the core material mixture to obtain thermally expandable microspheres.

[0035] The mass ratio of the core material mixture to the wall material solution is 1:0.6, and the amount of tetrahydrofuran added is 4 times the mass of polyurea.

[0036] Preparation Example 3 A method for preparing thermally expandable microspheres includes the following steps: S1. Using 1 kg of polyacrylonitrile fiber as the processing standard, the polyacrylonitrile fiber is crushed and ground to obtain polyacrylonitrile fiber powder with a particle size of 0.5-1.5 mm. S2. Then, at an ambient temperature of 15°C, liquid alkane n-pentane was added to the polyacrylonitrile fiber powder. The n-pentane completely submerged the polyacrylonitrile fiber powder. After impregnation for 4 hours under vacuum ultrasonic-assisted conditions (the ultrasonic generator was started under vacuum), the core material mixture was obtained by filtration. The vacuum ultrasonic conditions were: vacuum degree of 5 Pa and ultrasonic frequency of 30 kHz. S3. Polyurea and polyvinyl chloride are mixed in a mass ratio of 1:0.8 and dissolved in tetrahydrofuran to prepare a wall material solution. The wall material solution is then spray-dried onto the core material mixture to obtain thermally expandable microspheres.

[0037] The mass ratio of the core material mixture to the wall material solution is 1:0.8, and the amount of tetrahydrofuran added is 5 times the mass of polyurea.

[0038] Preparation Example 4 A method for preparing thermally expandable microcapsules is carried out according to the method in Preparation Example 1, except that in step S2, when the polyacrylonitrile fiber powder is impregnated in n-pentane, a mixed solvent of hydroxyl silicone oil, fluorocarbon surfactant and Tween 80 is added, and the mass ratio of hydroxyl silicone oil, fluorocarbon surfactant and polysorbate is 1:2.5:1.5, and the mixed solvent is 4 wt% of the amount of polyacrylonitrile fiber powder added.

[0039] Preparation Example 5 A method for preparing thermally expandable microcapsules is carried out according to the method in Preparation Example 1, except that in step S2, when the polyacrylonitrile fiber powder is impregnated in n-pentane, a mixed solvent of hydroxyl silicone oil, fluorocarbon surfactant and Tween 80 is added, and the mass ratio of hydroxyl silicone oil, fluorocarbon surfactant and polysorbate is 1:2:1, and the mixed solvent is 3 wt% of the amount of polyacrylonitrile fiber powder added.

[0040] Preparation Example 6 A method for preparing thermally expandable microcapsules is carried out according to the method in Preparation Example 1, except that in step S2, when the polyacrylonitrile fiber powder is impregnated in n-pentane, a mixed solvent of hydroxyl silicone oil, fluorocarbon surfactant and Tween 80 is added, and the mass ratio of hydroxyl silicone oil, fluorocarbon surfactant and polysorbate is 1:3:2, and the mixed solvent is 5 wt% of the amount of polyacrylonitrile fiber powder added.

[0041] Preparation Example 7 A method for preparing thermally expandable microcapsules is carried out according to the method in Preparation Example 1, except that in step S3, a wall material solution containing polyurea and polyvinyl chloride is spray-dried onto a core material mixture to form a first wall material, thereby obtaining primary thermally expandable microspheres. Sodium alginate is dissolved in water and spray-dried onto the surface of the primary thermally expandable microspheres to form a second wall material, thereby obtaining thermally expandable microspheres with n-pentane and polyacrylonitrile fiber powder as the core material, polyurea and polyvinyl chloride as the first wall material, and sodium alginate as the second wall material. The mass ratio of sodium alginate to water is 1:9, and the mass ratio of the mixture of sodium alginate and water to the wall material solution formed by polyurea, polyvinyl chloride, and tetrahydrofuran is 1:1.

[0042] Preparation Example 8 A method for preparing thermally expandable microcapsules is carried out according to the method in Preparation Example 1, except that in step S3, a wall material solution containing polyurea and polyvinyl chloride is spray-dried onto a core material mixture to form a first wall material, thereby obtaining primary thermally expandable microspheres. Sodium alginate is dissolved in water and spray-dried onto the surface of the primary thermally expandable microspheres to form a second wall material, thereby obtaining thermally expandable microspheres with n-pentane and polyacrylonitrile fiber powder as the core material, polyurea and polyvinyl chloride as the first wall material, and sodium alginate as the second wall material. The mass ratio of sodium alginate to water is 1:8, and the mass ratio of the mixture of sodium alginate and water to the wall material solution formed by polyurea, polyvinyl chloride, and tetrahydrofuran is 1:0.8.

[0043] Preparation Example 9 A method for preparing thermally expandable microcapsules is carried out according to the method in Preparation Example 1, except that in step S3, a wall material solution containing polyurea and polyvinyl chloride is spray-dried onto a core material mixture to form a first wall material, thereby obtaining primary thermally expandable microspheres. Sodium alginate is dissolved in water and spray-dried onto the surface of the primary thermally expandable microspheres to form a second wall material, thereby obtaining thermally expandable microspheres with n-pentane and polyacrylonitrile fiber powder as the core material, polyurea and polyvinyl chloride as the first wall material, and sodium alginate as the second wall material. The mass ratio of sodium alginate to water is 1:10, and the mass ratio of the mixture of sodium alginate and water to the wall material solution formed by polyurea, polyvinyl chloride, and tetrahydrofuran is 1:1.2.

[0044] Comparative Preparation Example 1 A method for preparing microspheres is carried out according to the method in Preparation Example 1, except that liquid pentane is not added to the core material.

[0045] Comparative Preparation Example 2 A method for preparing thermally expandable microspheres is carried out according to the method in Preparation Example 1, except that polyurea in the wall material raw material is replaced with polyvinyl chloride in equal amounts.

[0046] Comparative preparation example 3 A method for preparing thermally expandable microspheres is carried out according to the method in Preparation Example 1, except that polyvinyl chloride in the wall material raw material is replaced with polyurea in an equal amount.

[0047] Example 1 A method for preparing frost-resistant concrete includes the following steps: A preliminary mixture is prepared by mixing 250 kg of cement, 880 kg of coarse aggregate, 780 kg of fine aggregate, 70 kg of mineral powder, 50 kg of fly ash, 2 kg of air-entraining agent, 5 kg of waste aluminum particles, and 40 kg of polyacrylonitrile fiber. 2 kg of admixture and 2.5 kg of antifreeze were mixed and added to 110 kg of water. Then 5 kg of silane coupling agent KH-550 was added, and after mixing, the initial mixture was added. Finally, 30 kg of thermal expansion microspheres prepared in Preparation Example 1 were added, and after stirring, antifreeze concrete was obtained.

[0048] Among them, the admixture is polycarboxylate superplasticizer, and the air-entraining agent is sodium rosinate air-entraining agent.

[0049] Example 2 A method for preparing frost-resistant concrete includes the following steps: A preliminary mixture is prepared by mixing 200 kg of cement, 800 kg of coarse aggregate, 700 kg of fine aggregate, 60 kg of mineral powder, 40 kg of fly ash, 0.5 kg of air-entraining agent, 1 kg of waste aluminum particles, and 30 kg of polyacrylonitrile fiber. Mix 1 kg of admixture and 0.5 kg of antifreeze agent and add them to 100 kg of water. Then add 3 kg of silane coupling agent KH-550, mix, add the initial mixture, and finally add 20 kg of thermal expansion microspheres prepared in Preparation Example 2. Stir and the mixture is then used to prepare antifreeze concrete.

[0050] Among them, the admixture is polycarboxylate superplasticizer, and the air-entraining agent is sodium rosinate air-entraining agent.

[0051] Example 3 A method for preparing frost-resistant concrete includes the following steps: A preliminary mixture is prepared by mixing 300 kg of cement, 950 kg of coarse aggregate, 850 kg of fine aggregate, 80 kg of mineral powder, 60 kg of fly ash, 3.5 kg of air-entraining agent, 10 kg of waste aluminum particles, and 50 kg of polyacrylonitrile fiber. 3 kg of admixture and 3.5 kg of antifreeze were mixed and added to 120 kg of water. Then 8 kg of silane coupling agent KH-550 was added, and after mixing, the initial mixture was added. Finally, 40 kg of the thermal expansion microspheres prepared in Preparation Example 3 were added, and after stirring, antifreeze concrete was obtained.

[0052] Among them, the admixture is polycarboxylate superplasticizer, and the air-entraining agent is sodium rosinate air-entraining agent.

[0053] Example 4 A method for preparing antifreeze concrete is carried out according to the method in Example 1, except that waste aluminum particles are not added to the raw materials.

[0054] Examples 5-11 A method for preparing antifreeze concrete is carried out according to the method in Example 1, except that the thermal expansion microspheres are selected from those prepared in Examples 4-10.

[0055] Comparative Examples 1-3 A method for preparing antifreeze concrete is carried out according to the method in Example 1, except that the thermal expansion microspheres are selected from those prepared in Comparative Preparation Examples 1-3.

[0056] Comparative Example 4 A method for preparing antifreeze concrete is carried out according to the method in Example 1, except that the thermal expansion microspheres are replaced with an equal amount of polyacrylonitrile fibers.

[0057] Comparative Example 5 A method for preparing antifreeze concrete is carried out according to the method in Example 1, except that thermally expanding microspheres are not added to the raw materials.

[0058] Comparative Example 6 A method for preparing antifreeze concrete is carried out according to the method in Example 1, except that thermal expansion microspheres are replaced in equal amounts with a mixture of polyurea and polyvinyl chloride, and the mass ratio of polyurea to polyvinyl chloride is 1:0.7.

[0059] Performance testing The concrete prepared in the embodiments and comparative examples of this application was subjected to freeze-thaw cycle tests according to the rapid freeze-thaw cycle test method in GB / T50082-2009. The test results are shown in Table 1 below.

[0060] Table 1: Referring to the results in Table 1 above, the concrete prepared in the embodiments of this application has excellent freeze-thaw resistance. Referring to the test results of Examples 1 and 4, when waste aluminum particles were not added to the raw materials, its freeze-thaw resistance was reduced. Referring to the test results of Examples 1 and 5-7, when preparing the thermal expansion capsules, adding substances such as hydroxyl silicone oil when soaking polyacrylonitrile fiber powder with n-pentane further facilitates the wetting effect of n-pentane on polyacrylonitrile fiber powder, resulting in better freeze-thaw resistance of the final concrete. Combining the test results of Examples 8-10, after using polyurea and polyvinyl chloride as the first wall material, the addition of sodium alginate as the second wall material further improves the compatibility of thermal expansion microspheres with other raw materials and reduces the need for protection of the effective components of thermal expansion microspheres, ultimately improving the freeze-thaw resistance of the final concrete.

[0061] Combining the test results of Example 1 and Comparative Example 1, it can be seen that when no n-pentane is added to the microsphere core material, the freeze-thaw resistance of concrete is significantly reduced. Combining the test results of Comparative Example 2 and Comparative Example 3, when only polyurea or polyvinyl chloride is added to the wall material of the thermal expansion capsule, its freeze-thaw resistance is also reduced, which is related to the reduced protective effect of the wall material on the core material structure. Referring to the test results of Comparative Example 4 and Comparative Example 5, when no thermal expansion microspheres are added in Comparative Example 5, its freeze-thaw resistance is significantly reduced. However, when no thermal expansion microspheres are added in Comparative Example 4, and the amount of polyacrylonitrile fiber is increased, its freeze-thaw resistance is comparable to that of Comparative Example 5. When the amount of polyacrylonitrile fiber is increased to a certain level, its freeze-thaw resistance does not change significantly. Referring to the test results of Comparative Example 6, when the thermal expansion microcapsules are replaced with polyurea and polyvinyl chloride, its freeze-thaw resistance is increased compared to Comparative Example 5, but it is still weaker than the result of Example 1.

[0062] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A type of frost-resistant concrete, characterized in that, Including the following parts by weight of raw materials: 200-300 parts cement, 800-950 parts coarse aggregate, 700-850 parts fine aggregate, 100-120 parts water, 60-80 parts mineral powder, 40-60 parts fly ash, 1-3 parts admixture, 1-3 parts antifreeze, 0.5-3.5 parts air-entraining agent, 0-10 parts waste aluminum particles, 3-8 parts silane coupling agent, 30-50 parts polyacrylonitrile fiber, and 20-40 parts thermally expandable microspheres; The core material of the thermally expandable microspheres is polyacrylonitrile fiber powder and liquid alkane, and the wall material is a mixture of polyurea and polyvinyl chloride. The thermally expandable microspheres are prepared by the following method: Polyacrylonitrile fiber was crushed and ground to obtain polyacrylonitrile fiber powder. Then, liquid alkane was added at low temperature, and the mixture was impregnated for 2-4 hours under vacuum ultrasonic assistance and then filtered to obtain a core material mixture. Polyurea and polyvinyl chloride were dissolved in tetrahydrofuran to prepare a wall material solution. The wall material solution was then spray-dried onto a core material mixture to obtain thermally expanded microspheres. When preparing thermally expandable microspheres, during the impregnation of polyacrylonitrile fiber powder in liquid alkane, a mixed solvent of hydroxyl silicone oil, fluorocarbon surfactant, and polysorbate is added, with the mass ratio of hydroxyl silicone oil, fluorocarbon surfactant, and polysorbate being 1:(2-3):(1-2), and the mixed solvent being 3-5 wt% of the amount of polyacrylonitrile fiber powder added. The liquid alkane is selected from n-pentane or a mixture of n-pentane and n-hexane.

2. The antifreeze concrete according to claim 1, characterized in that: The mass ratio of the core material mixture to the wall material solution is 1:(0.6-0.8); the polyacrylonitrile fiber powder is completely immersed in liquid alkane, and the mass ratio of polyurea to polyvinyl chloride is 1:(0.6-0.8).

3. The antifreeze concrete according to claim 1, characterized in that: When impregnating polyacrylonitrile fiber powder in liquid alkane, the liquid alkane is added and the process is carried out at an ambient temperature of 5-15℃. The vacuum ultrasonic conditions are as follows: vacuum degree of 2-5 Pa and ultrasonic frequency of 20-30 kHz.

4. The antifreeze concrete according to claim 1, characterized in that: Primary thermal expansion microspheres are prepared by spray drying the wall material solution onto the core material mixture. Then, sodium alginate is dissolved in water and spray dried onto the surface of the primary thermal expansion microspheres to form thermal expansion microspheres.

5. The antifreeze concrete according to claim 1, characterized in that: The coarse aggregate is selected from crushed stone with a continuous particle size of 5-30mm, and the fine aggregate is selected from sand with a fineness modulus of 2.6-3.2; the fly ash is selected from Class F Grade I fly ash, and the mineral powder is selected from S95 grade mineral powder.

6. The antifreeze concrete according to claim 1, characterized in that: The admixture is a polycarboxylate superplasticizer, and the air-entraining agent is a rosin-based air-entraining agent.

7. The method for preparing frost-resistant concrete according to any one of claims 1-6, characterized in that: Includes the following steps: A preliminary mixture is prepared by mixing cement, coarse aggregate, fine aggregate, mineral powder, fly ash, air-entraining agent, waste aluminum particles, and polyacrylonitrile fiber. After mixing the admixture and antifreeze agent, add them to water, then add the silane coupling agent, mix again, add the initial mixture, and finally add the thermal expansion microspheres. Stir and then the antifreeze concrete is obtained.

Citation Information

Patent Citations

  • Nano-reinforced phase-change anti-freezing concrete mixture and preparation method thereof

    CN113185237A

  • High-strength anti-freezing macroporous recycled concrete as well as preparation method and application thereof

    CN116854432A

  • Concrete slurry and preparation method thereof

    CN117843305A